Warming up human body by nanoporous metallized polyethylene textile - Lili Cai (Nature Portfolio, 2017)
Energy wasted for heating the empty space of the entire building can be saved by passively heating the immediate environment around the human body. Here, the authors show a nanophotonic structure textile with tailored infrared property for passive personal heating using nanoporous metallized polyethylene.